Agatha Christie - Bloom, Harold (Philadelphia : Chelsea House Publishers, 2002)
Contains eleven essays in which various authors present critical evaluations of the life and works of mystery writer Agatha Christie.
Includes bibliographical references (p. 169-170) and index.
Young Adult.
Young Adult
Keywords: Christie, Agatha, -- 1890-1976 -- Criticism and interpretation; Christie, Agatha, -- 1890-1976 -- Criticism; Detective and mystery stories, English -- History and criticism; Women and literature -- England -- History -- 20th century; Mystery fiction -- History and criticism; Women and literature -- History